Assessment of trophic status of Ambazari Lake, Nagpur, India with emphasis to Macrozoobenthos as Bioindicator - Lonkar SS; Kedar GT; Tijare RV (International Journal of Life Sciences, 2015)
Assessment of macrozoobenthos and physicochemical parameters of Ambazari Lake of Nagpur from October 2010 to Sept. 2012 helps to reveal the trophic status of the lake. pH of Ambazari lake represented alkaline nature of lake. Macrozoobenthic diversity represented 28 species belonging to Phylum Annelida (22.68%), Arthropoda (21.63%) and Mollusca (55.68 %) represented by oligochaetes, decapodes, odonates, dipterans, gastropods and pelecypodes respectively. Seasonally, group Mollusca dominated the lake in summer season while winter season revealed the abundance of all the groups in more or less similar trend . Higher values of macrozoobenthic diversity as well as nutrients such as Sulphate, Phosphate and Nitrate values indicated oligomesotrophic status of lake.